Molecular engineering of dispersed nickel phthalocyanines on carbon nanotubes for selective CO2 reduction - Zhang, Xiao; Wang, Yang; Gu, Meng; Wang, Maoyu; Zhang, Zisheng; Pan, Weiying; Jiang, Zhan; Zheng, Hongzhi; Lucero, Marcos; Wang, Hailiang; Sterbinsky, George E.; Ma, Qing; et al. (Nature energy, 2020)
Electrochemical reduction of CO 2 is a promising route for sustainable production of fuels. A grand challenge is developing low-cost and efficient electrocatalysts that can enable rapid conversion with high product selectivity. Here we design a series of nickel phthalocyanine molecules supported on carbon nanotubes as molecularly dispersed electrocatalysts (MDEs), achieving CO 2 reduction performances that are superior to aggregated molecular catalysts in terms of stability, activity and selectivity. The optimized MDE with methoxy group functionalization solves the stability issue of the original nickel phthalocyanine catalyst and catalyses the conversion of CO 2 to CO with >99.5% selectivity at high current densities of up to −300 mA cm −2 in a gas diffusion electrode device with stable operation at −150 mA cm −2 for 40 h. The well-defined active sites of MDEs also facilitate the in-depth mechanistic understandings from in situ/operando X-ray absorption spectroscopy and theoretical calculations on structural factors that affect electrocatalytic performance. Widespread deployment of electrochemical CO 2 reduction requires low-cost catalysts that perform well at high current densities. Zhang et al. show that methoxy-functionalized nickel phthalocyanine molecules on carbon nanotubes can operate as high-performing molecularly dispersed electrocatalysts at current densities of up to −300 mA cm –2 .